Effect of Foot Reflexology on Arteriovenous Fistula Access Pain: A Randomized Clinical Trial - Seyedeh Faezeh Razavi; Azizeh Farshbaf-Khalili; Sakineh Goljarian; Hamid Tayebi Khosroshahi; Mohammad Gholipour; Alehe Seyedrasooli (Mashhad University of Medical Sciences, 2022)
Background: Hemodialysis is the most commonly used method for dialysis; nonetheless, it causes some problems, such as the pain associated with fistula needle insertion. Pain relief is one of the main skills of nurses, and reflexology can be used as a golden key for this puzzle.Aim: The present study aimed to assess the effect of foot reflexology on the pain of arteriovenous fistula (AVF) access.Method: This parallel double-blind clinical trial study was conducted on 50 female patients referring to Imam Reza Medical Center in Tabriz, Iran, in 2020-2021. The participants were randomly allocated to two groups of intervention and control using block randomization in a 1: 1 ratio. The intervention group received foot reflexology before hemodialysis for 20 min (10 min for each foot), while the control group received routine ward care. The data were collected through demographic characteristics and visual analog scale (VAS) questionnaires. Data were analyzed in SPSS 23.Results: In terms of place of residence, 96% and 88% of participants in the intervention and control groups lived in urban areas, respectively. Moreover, 72% and 64% of patients in the two groups of intervention and control had a history of hypertension, respectively. Furthermore, foot reflexology had a statistically significant effect on the mean score of pain intensity during three sessions of reflexology over time.Implications for Practice: It is recommended that foot reflexology be used to reduce the pain of needle entry into the arteriovenous fistula in hemodialysis patients since reflexology is non-invasive nursing care with an easy procedure and effective in pain relief.